Colorectal cancers: 12 year-results of a single center. Issue 2 (2013) - Küçüköner, Mehmet; Kaplan, Muhammed Ali; Inal, Ali; Urakci, Zuhat; Nas, Necip; Onder, Akin; Keles, Aysenur; Buyukbayram, Huseyin; Isikdogan, Abdurrahman
No abstract available